Anti-frosting performance of sprayable superhydrophobic coating suitable for outdoor coil of air source heat pump. (25th March 2020) - Wang, Feng; Zhou, Yuling; Yang, Weibo; Ni, Meiqin; Zhang, Xiaosong; Liang, Caihua
Highlights: Sprayable superhydrophobic surface was prepared by spraying SiO2 coating. The durability in frosting/defrosting cycles was greatly improved. Continuous self-jumping of droplet was achieved at early stage of frosting. Sprayable surface showed excellent anti-frosting performance. Sprayable surface was suitable for outdoor coil of air source heat pump. Abstract: Spraying method to prepare superhydrophobic surface is more efficient than the wet chemical etching used before, and is more suitable for outdoor coil of air source heat pump. However, durability in frosting/defrosting cycles and anti-frosting performance should be clarified before applying the sprayable superhydrophobic coating to solve the frosting problem. Superhydrophobic surface was prepared in this paper, by spraying SiO2 coating on aluminum surface. Frosting and defrosting tests were carried out to verify its durability and anti-frosting performance. The self-jumping of condensate droplets were focused on at early stage of frosting. Moreover, a theoretical model was developed to analyze the influence of the superhydrophobic surface characteristics on self-jumping of condensate droplets. The durability of the sprayable surface was greatly improved compared with the etched surface. Continuous self-jumping of condensate droplets was achieved at early stage of frosting, and theoretical analysis indicated that reducing contact angle hysteresis was the key to achieve self-jumping. Compared with the surface having equal contact angle but larger angle hysteresis, self-jumping reduced the surface coverage of droplets on the sprayable surface, as a result, decreasing the frost layer thickness by 33% after frosting for 60 min, which indicated that the sprayable surface had excellent anti-frosting performance.